فعالية استخدام طريقة الإشارات باليد لترقية إتقان المفردات بمعهد العصري: The Effectiveness of the Hand Gesture Method for Memorizing Mufrodat to Improve Arabic Vocabulary at the Modern Islamic Boarding School - Maulidia Nur Afifah; Abdal Chaqil Harimi; Djarfour Ibrahim (Journal of Arabic Language Teaching, 2026)
Many students in Islamic boarding schools struggle to memorize and retain Arabic vocabulary because of the dominance of conventional, repetition-based teaching methods. Prior research on multisensory and Total Physical Response (TPR) approaches suggests that integrating physical movement can enhance memory and engagement. However, empirical evidence in Islamic boarding school contexts remains limited. This study examines the effectiveness of the hand gesture method in improving Arabic vocabulary mastery at the Modern Islamic Boarding School Darussalam Purbalingga. A quantitative, quasi-experimental design was used, with an experimental group taught using hand gestures and a control group taught conventionally. Data were collected through pre- and post-tests and analyzed using normality and homogeneity tests, paired-sample t-tests, and N-Gain analysis. The experimental group achieved a significantly higher post-test mean score (84.09) than the control group (78.77). The paired-sample t-test yielded a significance value of 0.006 (<0.05), and the N-Gain score of 78.04% indicated high effectiveness. The study concludes that the hand gesture method effectively enhances Arabic vocabulary mastery by combining cognitive and physical learning activities. It is recommended that Islamic boarding schools adopt this innovative, interactive strategy to improve student engagement and vocabulary retention. يعاني الكثير من الطلاب في المعاهد الإسلامية من صعوبات في حفظ المفردات العربية واستبقائها بسبب غلبة الطرائق التقليدية القائمة على التكرار والحفظ المجرد. في حين تشير دراسات سابقة إلى أن دمج الحركة الجسدية في التعليم يعزز الذاكرة ويزيد التفاعل، إلا أن الأدلة التجريبية في بيئة المعاهد لا تزال محدودة. وتهدف هذه الدراسة إلى تحليل فعالية استخدام طريقة الإشارات باليد في ترقية إتقان المفردات العربية لدى طلاب معهد دار السلام الإسلامي العصري بوربالينغا. اعتمدت الدراسة المنهج الكمي بتصميم شبه تجريبي، حيث قسمت العينة إلى مجموعة تجريبية درست باستخدام طريقة الإشارات باليد، ومجموعة ضابطة درست بالطريقة التقليدية. جُمعت البيانات عن طريق الاختبار القبلي والبعدي، وحُللَت باستخدام اختبار الطبيعي والتجانس، واختبار (ت) للعينات المترابطة، وتحليل الكسب (N-Gain). أظهرت النتائج أن المجموعة التجريبية حققت متوسط درجات أعلى في الاختبار البعدي (84.09) مقارنة بالمجموعة الضابطة (78.77)، وكانت قيمة الدلالة (0.006) أقل من 0.05، وبلغت نسبة الكسب (78.04%)، مما يشير إلى فعالية عالية. تخلص الدراسة إلى أن طريقة الإشارات باليد فعالة في تحسين قدرة الطلاب على حفظ المفردات العربية وفهمها، من خلال الدمج بين النشاط الذهني والحركي. وتوصي المعاهد الإسلامية بتبني هذه الاستراتيجية التفاعلية المبتكرة لزيادة دافعية الطلاب وتعزيز الاحتفاظ بالمفردات.